THE EFFECT OF RELIGIOSITY AND LOVE OF MONEY ON ACCOUNTANT ETHICS CRISIS - Blasius Erik Sibarani; Citra Anggreani (Jurnal Akuntansi, 2023)
The problem in this study is that there are still violations of accountant ethics committed by accountants when carrying out their duties as an accountant. As a profession that carries out its functions, accountants must comply with professional ethics and carry out their duties in a certain way in accordance with professional ethics or established standards. Behavior that violates professional ethics is not only for public accountants, but also for government accountants and management accountants. If the accountant has the integrity to apply ethical and ethical values in the professional behavior of his work, then there should be no unethical behavior. The purpose of this study was to determine the effect of religiosity and love of money on accountants' ethical crisis. The sample used was determined by the purposive sampling method with certain criteria. Data analysis in this study used multiple linear regression and data collection techniques in this study in the form of a questionnaire. The data obtained were analyzed using the f test, t test, normality test, and multiple linear regression analysis. The results showed that religiosity and love of money simultaneously affected the ethical crisis of accountants. Partially, the religiosity variable has no effect on the accountant's ethical crisis, and love of money also has no effect on the accountant's ethical crisis.Keywords: Accountant Ethics Crisis, Love of Money, Religiosity